Determination of the necessary degree of national programs standardization by network and business planning methods - V. V. Eremin; S. B. Reshetnikov; D. V. Firsov (Вестник университета, 2021)
The article considers the application of methods that make it possible to determine the need for deeper standardization of processes within the framework of the implementation of national programs, based on the influence of the degree of standardization on the time and resource intensity of the implementation of national programs. To determine the impact of the degree of standardization on the implementation time of national programs implementation, it is proposed to use network-planning methods, taking into account the influence of the time required for the development and implementation of additional standards on the implementation of the national program. The impact of standardization on the resource intensity indicators of the implementation of national programs is proposed to be taken into account through the analysis of the dynamics of the amount of finance required for the implementation of the program. For this purpose, it is proposed to use business planning methods, namely: calculation of the costs associated with the development and implementation of additional standards and calculation of the financial benefits from deepening standardization, based on the calculation of the amount of reduction in the cost of financial resources per unit of the result of the national program implementation.